2022
DOI: 10.1002/saj2.20364
|View full text |Cite
|
Sign up to set email alerts
|

Molecular dynamics simulation of organic contaminant adsorption on organic‐coated smectite clay

Abstract: Molecular dynamics simulations are used to examine the adsorption and aggregation of tyrosine and glutamate molecules on a stack of smectite particles at three different organic loadings. The results reveal a strong affinity of the smectite surface for the organic molecules with the zwitterionic tyrosine molecules coating the exterior surfaces (and entering the interlayer region to a lesser extent), whereas the negatively charged glutamate molecules are generally found near the clay edge sites and in coordinat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 83 publications
0
4
0
Order By: Relevance
“…Then the one-stage electrostatic potential fitting with charge of each CMC unit restrained to be −1 (for the unprotonated carboxyl) was performed in Multiwfn to calculate the RESP2(0.5) charges of the head-monomer, body-monomer, and end-monomer separately, and the electrostatic potential distribution of the CMC molecule based on the above calculated atom charges was also illustrated by the Multiwfn, as summarized in Table S1. ,, Then the above calculated RESP2(0.5) charges were implemented for the CMC with a polymerization degree of 100. All the other parameters except partial charges (i.e., bond, angle, dihedral, and Lennard-Jones (LJ) 6–12 parameters) were generated by the web topology service TPPmktop based on the OPLS-AA force field whose effectiveness to describe the polymer and compatibility with CLAYFF force field has been well-tested by lots of researches. The interatomic parameters for water were based on the SPC/E model, those for Na + and Cl – were based on the well-established Smith and Dang model, and the Cu 2+ model proposed by Khanmohammadi was adopted in this study …”
Section: Simulation Methodsmentioning
confidence: 99%
“…Then the one-stage electrostatic potential fitting with charge of each CMC unit restrained to be −1 (for the unprotonated carboxyl) was performed in Multiwfn to calculate the RESP2(0.5) charges of the head-monomer, body-monomer, and end-monomer separately, and the electrostatic potential distribution of the CMC molecule based on the above calculated atom charges was also illustrated by the Multiwfn, as summarized in Table S1. ,, Then the above calculated RESP2(0.5) charges were implemented for the CMC with a polymerization degree of 100. All the other parameters except partial charges (i.e., bond, angle, dihedral, and Lennard-Jones (LJ) 6–12 parameters) were generated by the web topology service TPPmktop based on the OPLS-AA force field whose effectiveness to describe the polymer and compatibility with CLAYFF force field has been well-tested by lots of researches. The interatomic parameters for water were based on the SPC/E model, those for Na + and Cl – were based on the well-established Smith and Dang model, and the Cu 2+ model proposed by Khanmohammadi was adopted in this study …”
Section: Simulation Methodsmentioning
confidence: 99%
“…Thus, there is a need for mechanistic sorption prediction models that can precisely assess PFOS mobility in the environment under dynamic water chemistry conditions and electrostatic properties of the surface–solution interface. Such models can also benefit from increasingly available molecular-level insights on adsorption of per- and polyfluoroalkyl substances (PFAS) provided by spectroscopic analyses and molecular dynamics simulations. …”
Section: Introductionmentioning
confidence: 99%
“…A molecular dynamic (MD) simulation study of a phyllosilicate mineral particle stack and SOM molecules suggested that the mineral external surfaces display greater affinity towards zwitterionic tyrosine molecules while the clay edges, and aqueous and coordinating Ca ions, display affinity to negatively charged glutamate molecules. The study further revealed that these organic molecules are not effective in preventing adsorption of organic contaminants, such as dimethyl phthalate and perfluorbutanesulfonic acids, to the mineral surfaces (Willemsen et al., 2022). A comprehensive set of adsorption–desorption experiments coupled with molecular‐scale modeling were used by Glaser et al.…”
mentioning
confidence: 99%